Finance : capital markets, financial management, and investment management - Fabozzi, Frank J.; Peterson Drake, Pamela, 1954- (Frank J. Fabozzi series., 2009)
Created by the experienced author team of Frank Fabozzi and Pamela Peterson Drake, Finance examines the essential elements of this discipline and makes them accessible to a wide array of readers-from seasoned veterans looking for a review to newcomers needing to get their footing in finance. Divided into four comprehensive parts, this reliable resource opens with a detailed discussion of the basic tools of investing and financing decision-making-financial mathematics and financial analysis. After this informative introduction, you'll quickly become familiar with the three primary areas of fina.